Antibacterial Activity and Phytochemical Analysis of Edible Seaweed Eucheuma spinosum Against Staphyloccocus aureus - Anna Safitri; Arie Srihardyastutie; Anna Roosdiana; Sutrisno Sutrisno (Chemistry Department, The University of Brawijaya, 2018)
The current work aims to determine antibacterial activities of ethanol extracts of Eucheuma spinosum against Staphylococcus aureus. These were showed through inhibition zones formation, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) values. The MIC was determined using dilution test tube method, and the MBC was calculated using streaking method. Qualitative test was applied to determine phytochemical compounds in ethanol extract of E. spinosum. Results showed that ethanol extracts of E. spinosum at concentrations of 1%; 2%; 5%, and 10% (v/v) resulted in inhibition zones of 1.98; 4.14; 7.42; and 10.27 mm, respectively. In addition, concentration of 10% (v/v) was the MIC, and 15% (v/v) was the MBC values of E. spinosum extracts against S. aureus. The phytochemical analysis showed that alkaloids and saponins were the main components detected. Alkaloids positive tests were observed by the formation of brown sediment with Wagner’s reagent, yellow sediment with Mayer’s reagent, and orange sediment with Dragendorff’s reagent. Saponins positive results were detected by the formation of stable foam when the extracts reacted with water and HCl. Overall, these results suggested that E. spinosum extracts have antibacterial properties against Gram-positive bacteria, i.e. S. aureus.